Ferric chloride-induced murine carotid arterial injury: A model of redox pathology() - Li, Wei (Elsevier, 2013)
Ferric chloride (FeCl(3)) induced vascular injury is a widely used model of occlusive thrombosis that reports platelet activation in the context of an aseptic closed vascular system. This model is based on redox-induced endothelial cell injury, which is simple and sensitive to both anticoagulant and anti-platelets drugs. The time required for platelet aggregation to occlude blood flow gives a quantitative measure of vascular damage that is pathologically relevant to thrombotic disease. We have refined the traditional FeCl(3)-induced carotid artery model making the data highly reproducible with lower variation. This paper will describe our artifices and report the role of varying the oxidative damage by varying FeCl(3) concentrations and exposure. To explore a maximum difference between experimental groups, adjustment of the selected FeCl(3) dose and exposure duration may be necessary.